2017
DOI: 10.1111/dom.13116
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of the addition of ertugliflozin in patients with type 2 diabetes mellitus inadequately controlled with metformin and sitagliptin: The VERTIS SITA2 placebo‐controlled randomized study

Abstract: AimsTo assess ertugliflozin in patients with type 2 diabetes who are inadequately controlled by metformin and sitagliptin.Materials and MethodsIn this double‐blind randomized study (Clinicaltrials.gov NCT02036515), patients (glycated haemoglobin [HbA1c] 7.0% to 10.5% [53‐91 mmol/mol] receiving metformin ≥1500 mg/d and sitagliptin 100 mg/d; estimated glomerular filtration rate [eGFR] ≥60 mL/min/1.73 m2) were randomized to ertugliflozin 5 mg once‐daily, 15 mg once‐daily or placebo. The primary efficacy endpoint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
202
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 129 publications
(225 citation statements)
references
References 26 publications
19
202
0
4
Order By: Relevance
“…5,7 It is likely to be used in combination with a number of other antihyperglycemic and lipid-lowering agents (eg, statins) for comorbidities associated with diabetes. 5,7 It is likely to be used in combination with a number of other antihyperglycemic and lipid-lowering agents (eg, statins) for comorbidities associated with diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,7 It is likely to be used in combination with a number of other antihyperglycemic and lipid-lowering agents (eg, statins) for comorbidities associated with diabetes. 5,7 It is likely to be used in combination with a number of other antihyperglycemic and lipid-lowering agents (eg, statins) for comorbidities associated with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…5,7,22,23 Coadministration of ertugliflozin with sitagliptin 100 mg provided greater glycemic control compared with each individual dose of ertugliflozin and sitagliptin with inadequate control on either metformin or diet and exercise. 5,7,22 Due to the linear and time-independent PK of ertugliflozin, single-dose PK are predictive of multiple-dose PK of ertugliflozin. 23 Ertugliflozin as an add-on to metformin, and metformin and sitagliptin, also provided clinically meaningful body weight and systolic blood pressure reductions.…”
Section: Discussionmentioning
confidence: 99%
“…Data for this post hoc analysis were pooled from three randomized, double‐blind, multicenter, placebo‐controlled, Phase 3 studies (VERTIS SITA2, VERTIS MET, VERTIS MONO) of a total of 1,544 patients with T2DM treated with ertugliflozin or placebo. Studies had similar overall study populations, designs, and enrollment criteria (Supporting Information Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Recent phase III trials have demonstrated that ertugliflozin is associated with statistically significant reductions in hemoglobin A1c, fasting plasma glucose, and body weight when used as monotherapy (compared with placebo),3 and when added to sitagliptin4 or metformin plus sitagliptin 5. When dosed in the fasting state, ertugliflozin pharmacokinetics are characterized by rapid absorption following oral administration (with median time to maximum concentration (T max ) occurring at 0.5–1.5 h postdose), dose proportionality in exposure (area under the curve (AUC) and maximum concentration (C max )) over a dose range of 0.5–300 mg, and a terminal elimination half‐life (t 1/2 ) of 11–17 h 1.…”
mentioning
confidence: 99%